Mengembangkan Bakat Ekonomi:Investasi dalam Sumber Daya Manusia untuk Pertumbuhan Bisnis - Ainurrohmah, Cindy (Maliki Interdisciplinary Journal, 2025)
Investment in human resources (HR) is a crucial foundation for driving sustainable business growth in the digital economy era. Enhancing economic talent—particularly in terms of skills, education, and productivity—is key to creating competitive advantages for companies. This article aims to analyze the role of HR investment in economic talent development and its impact on business growth. The method used is a literature review from various scientific journals published in the last 10 years. The analysis reveals that companies investing in training, competency development, and talent management tend to have higher productivity, improved employee loyalty, and stronger competitiveness in the global market. Therefore, economic talent development strategies should be prioritized in long-term business planning.